Polyphosphoric acid-polymer composite modified asphalt and preparation method thereof
Through the technical means of polyphosphate-polymer composite modified asphalt, the problem of insufficient crack resistance and ductility of asphalt under low temperature conditions in the prior art is solved, and better low-temperature performance and stability are achieved, and it is suitable for a wide range of pavement applications.
Patent Information
- Application Number
- CN202510664796.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-22
- Publication Date
- 2025-06-20
- Estimated Expiration
- 2045-05-22
AI Technical Summary
The existing polymer modified asphalt has insufficient crack resistance and ductility under low temperature conditions, resulting in brittle crust and arching on the road surface, and excessive viscosity during construction leads to separation problems.
Polyphosphate-polymer composite modified asphalt is used to enhance dispersion through reaction of polyphosphate with asphalt molecules, forming a "dual network" structure to improve elastic recovery and shear resistance, and bio-based plasticizers and nano-enhanced fillers are added to improve low-temperature performance and stability.
It significantly improves the low-temperature crack resistance and storage stability of asphalt, solves the problems of embrittlement and arching of road surfaces at low temperatures, and reduces the viscosity during construction, avoiding separation.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This application relates to the technical field of pavement engineering materials, and particularly relates to a polyphosphoric acid-polymer composite modified asphalt and a preparation method thereof. Background Art
[0002] Polymer modified asphalt is widely used in highway, airport runway, bridge and building waterproofing projects. Due to its excellent high and low temperature performance, it can significantly improve the pavement performance and service life, and meet the requirements of complex climate and heavy traffic.
[0003] Common modifiers such as SBS (styrene-butadiene-styrene triblock copolymer) and SBR (styrene-butadiene rubber) modified asphalt make the modified asphalt have excellent high temperature rutting resistance, low temperature cracking resistance, fatigue resistance and excellent elastic recovery ability. It is mainly applied to high-grade pavements such as the upper layer of highways, sections with heavy traffic and many overloaded vehicles. Based on the above excellent road performance, SBS modified asphalt has become the mainstream product in modified asphalt. However, the addition amount of SBS is too large, the cost is too high, and due to the unsaturated double bonds in its molecular structure, the weather resistance and anti-aging performance are poor. At the same time, polyphosphoric acid (PPA) is a low-cost asphalt modifier widely used in polymer modified asphalt. The addition of PPA can significantly improve the high temperature performance of SBS and SBR modified asphalt, but polyphosphoric acid modified asphalt has insufficient low temperature ductility and crack resistance. Under low temperature conditions, the pavement is prone to embrittlement and crusting, the asphalt mixture arches up, losing the pavement flatness, and there is also the problem of segregation due to too high viscosity during construction. Summary of the Invention
[0004] This application provides a polyphosphoric acid-polymer composite modified asphalt and a preparation method thereof to solve the above problems mentioned in the background art.
[0005] This application provides a polyphosphoric acid-polymer composite modified asphalt, and the raw materials include the following components by weight: 100 parts by weight of matrix asphalt, 0.5 - 3 parts by weight of polyphosphoric acid, 0.1 - 0.5 parts by weight of stabilizer, 2 - 5 parts by weight of bio-based plasticizer, 5 - 15 parts by weight of elastomer particles, 0.5 - 2 parts by weight of nano-enhanced filler, 1 - 5 parts by weight of SEBS, 2 - 5 parts by weight of APAO, 1 - 3 parts by weight of organic montmorillonite.
[0006] Optionally, 0.05 - 0.4 parts by weight of anti-cracking agent is further added to the asphalt, and the anti-cracking agent is obtained by mixing nonylphenol polyoxyethylene ether, benzoic anhydride and 1-amino-8-naphthol-4,6-disulfonic acid in a mass ratio of 1:0.55 - 4.5:1 - 2.5.
[0007] Optionally, the polyphosphoric acid is an industrial pure reagent, and its purity is not less than 85% calculated as phosphorus pentoxide content.
[0008] Optionally, the stabilizer is selected from sulfur or an organosilane coupling agent.
[0009] Optionally, the bio-based plasticizer is selected from epoxy soybean oil acrylate.
[0010] Optionally, the epoxy value of the epoxy soybean oil acrylate is 6.0% - 6.5%.
[0011] Optionally, the elastomer particles are selected from activated rubber powder, and the particle size of the activated rubber powder is 80 - 120 mesh.
[0012] Optionally, the nano-enhanced filler includes at least one of graphene oxide and nano-zinc oxide.
[0013] Optionally, the matrix asphalt includes one or more of 70# matrix asphalt, 110# matrix asphalt, 130# matrix asphalt and 140# matrix asphalt.
[0014] On the other hand, the present application provides a method for preparing a polyphosphoric acid-polymer composite modified asphalt, which is used to prepare the above-mentioned modified asphalt, and the preparation method includes the following steps: (1) By weight, heat the matrix asphalt to 160 - 170 °C, add polyphosphoric acid to the matrix asphalt, and shear at a speed of 5000 - 5500 r / min until evenly dispersed. After the shearing is completed, develop at 165 °C for 30 min; (2) Heat the asphalt obtained in step (1) to 170 - 180 °C, add a bio-plasticizer and a stabilizer by weight, and stir at a speed of 5000 - 5500 r / min for 30 min; (3) By weight, add activated rubber powder, SEBS and APAO to the asphalt obtained in step (2), and maintain a high-speed shearing rate of 180 °C and 5000 r / min for 1 h; (4) By weight, add benzoic anhydride to the asphalt obtained in step (3), stir at a speed of 3000 - 5000 r / min for 5 - 10 min, then add nonylphenol polyoxyethylene ether and 1-amino-8-naphthol-4,6-disulfonic acid, and stir at a speed of 5000 - 5500 r / min for 20 - 30 min; (5) Add nano-fillers and organic montmorillonite to the asphalt obtained in step (4), and maintain a high-speed shearing rate of 180 °C and 5000 - 5500 r / min for 2 h. After the shearing is completed, develop at 170 - 180 °C for 2 h to obtain a polyphosphoric acid-polymer composite modified asphalt.
[0015] The polyphosphoric acid-polymer composite modified asphalt provided by this application and its preparation method achieve the preparation of polyphosphoric acid-polymer composite modified asphalt. Compared with the prior art, it has the following beneficial effects: (1) In this application, polyphosphoric acid reacts with the active sites in asphalt molecules, enhancing the dispersion of asphaltenes in the soft components of asphalt. The information cross-linked structure, lipophilic groups, and polyanionic group structure in its molecular structure endow it with good adhesion and passivation effects in asphalt. At the same time, chemical cross-linking increases the elastic recovery ability of asphalt, thereby improving the stability and shear resistance of asphalt. The synergistic effect of SEBS and PPA forms a "dual network" structure. The PPA cross-linked network provides rigid support, and the SEBS elastic network absorbs energy, jointly restricting the orientation and recombination of asphalt molecular chains. Elastomer particles significantly improve the crack resistance and toughness of asphalt at low temperatures. At the same time, combined with SEBS, they entangle with each other in the matrix asphalt, increasing the asphalt viscosity and forming a relatively stable cross-linked structure, thus enhancing the low-temperature crack resistance and storage stability. Moreover, a synergistic effect is formed among polyphosphoric acid (PPA), bio-based plasticizers, and elastomer particles. Bio-based plasticizers can improve the compatibility and miscibility of modified asphalt, effectively interact with the asphalt matrix, and improve its compatibility with SEBS and elastomer particles. At the same time, it greatly reduces the viscosity of asphalt after the incorporation of elastomer particles, improves the segregation-related problems caused by excessive viscosity during construction, and helps to reduce phase separation and delamination in modified asphalt, improving the stability and consistency of modified asphalt.
[0016] (2) By adding crack-resistant agents, including nonylphenol polyoxyethylene ether, benzoic anhydride, and 1-amino-8-naphthol-4,6-disulfonic acid, the hydroxyl groups contained in nonylphenol polyoxyethylene ether react with the surface active groups of asphalt, causing the long-chain alkyl groups to be free on the outer side of asphalt particles. Some of the amino, hydroxyl, and sulfonic acid groups in 1-amino-8-naphthol-4,6-disulfonic acid react with the active sites on the surface of asphalt. At the same time, the long-chain alkyl groups of nonylphenol polyoxyethylene ether are more likely to attack the surface of asphalt than 1-amino-8-naphthol-4,6-disulfonic acid. Therefore, the remaining 1-amino-8-naphthol-4,6-disulfonic acid is wrapped on the outer surface of the asphalt particles modified by SEBS and PPA, and a multiphase composite structure is formed between each modifier and asphalt. When the modified asphalt is used in a low-temperature environment, the composite structures can buffer the stress generated by low temperature with each other, thereby improving the low-temperature performance of the modified asphalt and reducing the embrittlement and cracking of the modified asphalt due to temperature reduction. Benzoic anhydride is also used to adjust the acidity and alkalinity during the preparation of the modified asphalt, keeping the pH value of the system between 5.5 and 7 before adding nonylphenol polyoxyethylene ether and 1-amino-8-naphthol-4,6-disulfonic acid, which helps the reaction of nonylphenol polyoxyethylene ether and 1-amino-8-naphthol-4,6-disulfonic acid with asphalt and facilitates the stable formation of the multiphase composite structure to ensure the low-temperature stability and crack resistance of the modified asphalt.
[0017] (3) The modified asphalt provided by this application has a simple and fast preparation method, which can be completed only with simple stirring equipment. Moreover, it not only retains good high-temperature performance but also improves low-temperature performance. Therefore, the modified asphalt provided by this application can be applied in a wider range and can be mass-produced. Detailed implementation manners
[0018] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions in the embodiments of this application will be described clearly and completely below. Obviously, the described embodiments are some but not all of the embodiments of this application. Based on the embodiments in this application, all other embodiments obtained by those of ordinary skill in the art without creative efforts also belong to the scope of protection of this application.
[0019] This application provides a polyphosphoric acid-polymer composite modified asphalt, and the raw materials include the following components by weight: 100 parts by weight of matrix asphalt, 0.5 - 3 parts by weight of polyphosphoric acid, 0.1 - 0.5 parts by weight of stabilizer, 2 - 5 parts by weight of bio-based plasticizer, 5 - 15 parts by weight of elastomer particles, 0.5 - 2 parts by weight of nano-enhancing filler, 1 - 5 parts by weight of SEBS, 2 - 5 parts by weight of APAO, and 1 - 3 parts by weight of organic montmorillonite.
[0020] Specifically, in the present application, the non-reactive butadiene segments in the SEBS molecule are used to reduce the stiffness caused by oxidation, improve flexibility, and enhance the anti-aging performance. At the same time, the problems of insufficient low-temperature ductility and anti-cracking performance of polyphosphoric acid-modified asphalt are solved. The use of organic montmorillonite and nano-enhanced fillers improves the storage stability of SEBS-modified asphalt. As a compatibilizer, epoxy soybean oil not only enhances the compatibility and miscibility of the modified asphalt, but also significantly reduces the viscosity after the incorporation of rubber powder, solves the segregation problem caused by excessive viscosity during construction, improves the compatibility with SEBS and rubber powder, reduces phase separation and delamination phenomena, and enhances the stability of the modified asphalt.
[0021] Polyphosphoric acid (PPA) is a water-soluble polymer substance that can softly bind to the surface of asphalt particles to form a film layer, blocking the penetration of oxygen and moisture, effectively extending the service life of asphalt, and improving the durability and maintainability of the road surface. PPA reacts with the active sites (hydroxyl groups, imino groups, sulfhydryl groups) in the asphalt molecule, breaking the asphaltene clusters, enhancing the dispersion of asphaltenes in the soft components of asphalt. Stable spatial grids can be formed between the dispersed asphaltenes. The special structures such as the information cross-linking structure, lipophilic groups, and polyanion groups in its molecular structure endow it with good adhesion and passivation effects in asphalt. At the same time, it increases the elastic recovery ability of asphalt through chemical cross-linking, reduces the initial stress value, and can increase the intermolecular interaction force, thereby improving the stability and anti-shear performance of asphalt.
[0022] The physical network of SEBS (styrene-ethylene / butylene-styrene block copolymer) can maintain an elastic skeleton at high temperatures and delay the irreversible deformation of molecular chains. In addition, PPA can effectively improve the storage stability of polymer-modified asphalt by increasing the interfacial energy between the matrix asphalt and SEBS molecules by preventing SEBS aggregation. The synergistic effect of SEBS and PPA forms a "dual network" structure. The PPA cross-linking network provides rigid support, and the SEBS elastic network absorbs energy, jointly restricting the orientation and recombination of asphalt molecular chains. The SEBS molecules in the modified asphalt can still maintain partial elasticity after aging, improving the low-temperature deformation ability of the modified asphalt.
[0023] SEBS (styrene-ethylene-butylene-styrene) is a polymer obtained by hydrogenating SBS (styrene-butadiene-styrene). SEBS is a polymer modifier prepared by hydrogenating the unsaturated carbon-carbon double bonds of SBS. Its molecular chain contains almost no unsaturated double bonds, has good heat resistance, excellent antioxidant and anti-ultraviolet aging performance. The styrene content is 35%, the hardness is 72, the tensile stress is greater than 5.50 MPa, and the elongation at break is greater than 500%.
[0024] The addition of stabilizers can improve the anti-aging and antioxidant properties of modified asphalt. It also has a powerful antioxidant and anti-aging effect, which can prevent oxidation reactions and the breakage of molecular chains in asphalt. Bio-based plasticizers can improve the low-temperature performance, water stability and environmental friendliness of asphalt. By improving the flexibility, ductility and plasticity of asphalt, bio-based plasticizers make it softer, thereby reducing the incidence of pavement cracking and warping and enhancing its crack resistance under low-temperature conditions.
[0025] Elastomer particles are evenly dispersed in the matrix asphalt, which can significantly improve the crack resistance and toughness of asphalt at low temperatures, enabling the modified asphalt to be widely applicable in cold regions. At the same time, when the modified asphalt is subjected to external forces, it can quickly return to its original state, improving the waterproof performance of the modified asphalt.
[0026] Nano-enhanced fillers have a high specific surface area and can be evenly dispersed in asphalt. At the same time, they adsorb asphalt particles, which can significantly enhance the elastic modulus and deformation resistance of modified asphalt, improve the mechanical properties of modified asphalt, and also improve the durability and anti-aging performance of asphalt. Moreover, nano-enhanced fillers can significantly enhance the self-healing ability of asphalt, enhancing its fatigue resistance, rutting resistance and crack resistance.
[0027] Using APAO (amorphous α-olefin copolymer) and SEBS to compound-modify asphalt can effectively improve the anti-aging performance of asphalt. By adding APAO, the dosage of SEBS can be reduced to reduce costs, and it has good compatibility with asphalt. The two are compounded to improve the anti-aging performance of asphalt, reducing pavement diseases caused by asphalt aging under high-temperature climate conditions in summer in hot regions. The APAO selected is the VESTOPLAST 828 type APAO modifier, which is a colorless granular solid.
[0028] Organic montmorillonite is mixed with asphalt by the intercalation method, which can significantly improve the high-temperature performance, anti-aging performance and barrier performance of asphalt. Due to the poor compatibility between SEBS and asphalt, the segregation phenomenon of SEBS-modified asphalt is relatively serious. After adding organic montmorillonite (OMMT), the thermal storage stability of SEBS-modified asphalt is significantly improved, and at the same time, the performance of SEBS-modified asphalt after aging is improved. Through the above solution, the present application realizes the preparation of polyphosphoric acid-polymer composite modified asphalt. By reacting polyphosphoric acid with the active sites (hydroxyl group, imino group, sulfhydryl group) in asphalt molecules, the asphaltene clusters are broken, the dispersion degree of asphaltenes in the soft component of asphalt is enhanced, and stable spatial grids can be formed between the dispersed asphaltenes. The information cross-linking structure, lipophilic group and polyanion group structure in its molecular structure endow it with good adhesion and passivation effect in asphalt. At the same time, the elastic recovery ability of asphalt is increased by chemical cross-linking, the initial stress value is reduced, and the intermolecular interaction force can be increased, thereby improving the stability and shear resistance of asphalt. The synergistic effect of SEBS and PPA forms a "dual network" structure. The PPA cross-linking network provides rigid support, and the SEBS elastic network absorbs energy, jointly restricting the orientation and recombination of asphalt molecular chains. The SEBS molecules in the modified asphalt can still maintain partial elasticity after aging, improving the low-temperature deformation ability of the modified asphalt. The elastomer particles significantly improve the crack resistance and toughness of asphalt at low temperature. At the same time, combined with SEBS, they are intertwined in the matrix asphalt, increasing the asphalt viscosity at the same time, forming a relatively stable cross-linked structure, thereby enhancing the low-temperature crack resistance and storage stability. And a synergistic effect is formed among polyphosphoric acid (PPA), bio-based plasticizer compatibilizer and elastomer particles. The bio-based plasticizer can improve the compatibility and miscibility of the modified asphalt, can effectively interact with the asphalt matrix, and improve its compatibility with SEBS and elastomer particles. At the same time, it greatly reduces the viscosity of the asphalt after the incorporation of elastomer particles, improves the segregation-related problems caused by too high viscosity during construction, and helps to reduce the phase separation and delamination phenomena in the modified asphalt, improving the stability and consistency of the modified asphalt.
[0029] Optionally, 0.05-0.4 parts by weight of a crack inhibitor is further added to the asphalt. The crack inhibitor is obtained by mixing nonylphenol polyoxyethylene ether, benzoic anhydride and 1-amino-8-naphthol-4,6-disulfonic acid in a mass ratio of 1:0.55-4.5:1-2.5.
[0030] Specifically, the crack-resistant agent forms a stable multi-phase composite structure by mixing with asphalt. The phases cooperate with each other, which can improve the tensile strength and crack resistance of the asphalt mixture and reduce the cracking phenomenon of the road surface. The crack-resistant agent includes nonylphenol polyoxyethylene ether, benzoic anhydride and 1-amino-8-naphthol-4,6-disulfonic acid. The nonylphenol polyoxyethylene ether contains long-chain alkanes, and the 1-amino-8-naphthol-4,6-disulfonic acid contains aromatic rings. The hydroxyl groups contained in the nonylphenol polyoxyethylene ether can react with the surface active groups of asphalt, making the long-chain alkyl groups free outside the asphalt particles. At the same time, the amino, hydroxyl and sulfonic acid groups in part of the 1-amino-8-naphthol-4,6-disulfonic acid react with the active sites on the surface of asphalt to further modify the asphalt. At the same time, the long-chain alkyl groups of nonylphenol polyoxyethylene ether are more likely to attack the surface of asphalt than 1-amino-8-naphthol-4,6-disulfonic acid. Therefore, the remaining 1-amino-8-naphthol-4,6-disulfonic acid is wrapped on the outer surface of the asphalt particles modified by SEBS and PPA. A multi-phase composite structure is formed between each modifier and asphalt. When the modified asphalt is used in a low-temperature environment, the composite structures can buffer the stress generated by low temperature with each other, thereby improving the low-temperature performance of the modified asphalt and reducing the embrittlement and cracking of the modified asphalt due to temperature reduction.
[0031] Meanwhile, benzoic anhydride is used to adjust the acidity and alkalinity during the preparation of the modified asphalt, keeping the pH value of the system between 5.5 and 7 before adding nonylphenol polyoxyethylene ether and 1-amino-8-naphthol-4,6-disulfonic acid, which helps the reaction of nonylphenol polyoxyethylene ether and 1-amino-8-naphthol-4,6-disulfonic acid with asphalt and facilitates the stable formation of the multi-phase composite structure to ensure the low-temperature stability and crack resistance of the modified asphalt.
[0032] Moreover, by controlling the mass ratio of nonylphenol polyoxyethylene ether, benzoic anhydride and 1-amino-8-naphthol-4,6-disulfonic acid, that is, controlling the addition ratio of long-chain alkyl groups and aromatic rings in the crack-resistant agent, it is avoided that excessive addition of aromatic rings leads to too high rigidity of the modified asphalt, which is not conducive to the deformation of asphalt at low temperature, and thus the low-temperature crack resistance of the modified asphalt can be improved. Optionally, the polyphosphoric acid is an industrial pure reagent, and the purity is not less than 85% calculated by phosphorus pentoxide content.
[0033] Optionally, the stabilizer is selected from sulfur or an organosilicon coupling agent.
[0034] Specifically, the stabilizer can improve the anti-aging performance and antioxidant performance of the modified asphalt, can prevent the oxidation reaction and the breakage of molecular chains in the asphalt. It can react with free radicals and oxidation products in the asphalt to form stable compounds, effectively delaying the aging process of the modified asphalt, enhancing the anti-dissolution performance of the modified asphalt, reducing its fluidity under high-temperature conditions, and improving the stability and durability of the road surface.
[0035] Among them, the silicone coupling agent is selected from at least one of amino-silane coupling agents (such as N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane), epoxy-silane coupling agents (such as glycidyl ether oxypropyltrimethoxysilane), vinyl-silane coupling agents (such as vinyltrimethoxysilane, CAS No. 2768-02-7), and methacryloxy-silanes (such as γ-methacryloxypropyltrimethoxysilane).
[0036] Optionally, the bio-based plasticizer is selected from epoxy soybean oil acrylate.
[0037] Optionally, the epoxy value of the epoxy soybean oil acrylate is 6.0% - 6.5%.
[0038] Specifically, as a compatibilizer, the bio-based plasticizer can improve the compatibility and miscibility of the modified asphalt, and at the same time greatly reduce the viscosity of the asphalt after the incorporation of elastomer particles, improving the segregation-related problems caused by excessive viscosity during construction. At the same time, it can effectively interact with the asphalt matrix, improving its compatibility with SEBS and elastomer particles. This helps to reduce phase separation and delamination in the modified asphalt, further improving the stability and consistency of the modified asphalt.
[0039] The application of the bio-based plasticizer can also enhance the environmental performance of the asphalt. The bio-based material in this application is selected from epoxy soybean oil acrylate, which is biodegradable, can reduce the dependence on petrochemical resources, reduce environmental pollution, and reduce the negative impact on the environment. It has high compatibility with other components, improved processing performance and mechanical properties, can improve the ductility and plasticity of the asphalt, making it softer, thereby reducing the incidence of pavement cracking and warping.
[0040] The bio-based plasticization provides a certain relative movement ability between the three-dimensional network structure formed by the nano-enhanced filler, PPA and the asphalt and the free asphalt molecules. When the nano-enhanced filler and PPA form an integral part in part of the matrix asphalt, while improving the overall strength, it also gives it a certain fluidity and flexibility, thereby improving its rheological properties at low temperatures, so that it will not be too brittle at too low temperatures to cause pavement cracking and generate cracks, and can improve its fatigue resistance.
[0041] Optionally, the elastomer particles are selected from activated rubber powder, and the particle size of the activated rubber powder is 80 - 120 mesh.
[0042] Optionally, the nano-enhanced filler includes at least one of graphene oxide and nano-zinc oxide.
[0043] Specifically, after incorporating graphene oxide, the penetration of asphalt decreases, and it has a higher softening point and ductility, improving various properties of asphalt. Nano-graphene is used to compound-modify the active crumb rubber modified asphalt. After modification, the crumb rubber is fully wrapped by asphalt, and the swelling and adsorption phenomenon is obvious. It has better compatibility with asphalt and enhances the interfacial bonding between asphalt and crumb rubber. Graphene oxide is made from 40-50um flaky graphite, and its specific surface area is 2500-5000m 2 / g. If the specific surface area of graphene oxide is too large, it will be difficult to disperse during the modification process and agglomeration will occur, failing to achieve the purpose of modifying asphalt. If the specific surface area is too small, the compatibility between graphene oxide and asphalt will be poor, and segregation is likely to occur. Among them, the method for preparing graphene oxide from flaky graphite is made by the existing technology well-known to those skilled in the art (such as obtained by oxidation with strong acid and potassium permanganate, or obtained by electrochemical oxidation method, ensuring its specific surface area is 2500-5000m 2 / g is sufficient, which is the existing technology and not the innovation point of this application, so it will not be elaborated here.
[0044] Nano-zinc oxide can enhance the diffusion ability of polyphosphoric acid in matrix asphalt, making the cyclization and grafting reaction between polyphosphoric acid and asphalt components more sufficient, and further enhancing the rutting resistance of polyphosphoric acid modified asphalt used in high-temperature areas. Nano-enhanced fillers can also improve the storage stability, anti-aging performance and durability of modified asphalt. Among them, nano-zinc oxide is white hexagonal crystal or spherical particles, and its zinc oxide content is greater than 99.0%.
[0045] Optionally, the matrix asphalt includes one or more of 70# matrix asphalt, 110# matrix asphalt, 130# matrix asphalt and 140# matrix asphalt.
[0046] On the other hand, this application provides a preparation method of polyphosphoric acid-polymer composite modified asphalt, which is used to prepare the above-mentioned modified asphalt. The preparation method includes the following steps: (1) By weight, heat the matrix asphalt to 160-170°C, add polyphosphoric acid to the matrix asphalt, and shear at a high speed of 5000-5500r / min until evenly dispersed. After the shearing ends, develop at 165°C for 30min; (2) Heat the asphalt obtained in step (1) to 170-180°C, add a biological plasticizer and a stabilizer by weight, and stir at a speed of 5000-5500r / min for 30min; (3) By weight, add activated crumb rubber, SEBS and APAO to the asphalt obtained in step (2), and maintain a high-speed shearing rate of 180°C and 5000r / min for 1h; (4) By weight parts, add benzoic anhydride to the asphalt obtained in step (3), stir at a speed of 3000 - 5000 r / min for 5 - 10 min, then add nonylphenol polyoxyethylene ether and 1 - amino - 8 - naphthol - 4,6 - disulfonic acid, and stir at a speed of 5000 - 5500 r / min for 20 - 30 min; (5) Add nano - filler and organic montmorillonite to the asphalt obtained in step (4), and maintain a high - speed shear at 180 °C and a speed of 5000 - 5500 r / min for 2 h. After the shear is completed, develop at 170 - 180 °C for 2 h to obtain polyphosphoric acid - polymer composite modified asphalt.
[0047] Specifically, first heat the base asphalt to 160 - 170 °C to increase the temperature, which is convenient for the subsequent reaction of polyphosphoric acid with the active groups on the surface of the asphalt. Under high - speed shear, uniformly mix polyphosphoric acid and the base asphalt to improve the efficiency of the modification reaction. Then develop at 165 °C for 30 min to make the reaction between polyphosphoric acid and the base asphalt more sufficient. Then mix and react the activated rubber powder, SEBS and APAO with the asphalt modified by polyphosphoric acid. When adding the anti - cracking agent, first add benzoic anhydride and stir to mix, keep the pH value of the reaction system between 5.5 - 7, then add nonylphenol polyoxyethylene ether and 1 - amino - 8 - naphthol - 4,6 - disulfonic acid for reaction. A multi - phase composite structure is formed between each modifier and the asphalt. The composite structures can relieve the temperature sensitivity and buffer the stress generated by low temperature with each other, thereby improving the low - temperature performance of the modified asphalt and reducing the embrittlement and cracking of the modified asphalt due to temperature reduction. Finally, add nano - filler and organic montmorillonite. The nano - filler and organic montmorillonite have small particle sizes and large specific surface areas, and can be further dispersed in the modified asphalt and enter the multi - phase composite structure, reducing the viscosity of the modified asphalt and improving the high - temperature and low - temperature performance of the modified asphalt.
[0048] The following takes specific examples to illustrate the technical solutions of the present application in detail.
[0049] Example 1 A preparation method of polyphosphoric acid - polymer composite modified asphalt, the preparation method includes the following steps: (1) Heat 100 weight parts of base asphalt to 160 °C, add 0.5 weight part of polyphosphoric acid to the base asphalt, and high - speed shear at a speed of 5000 r / min until evenly dispersed. After the shear is completed, develop at 165 °C for 30 min; (2) Heat the asphalt obtained in step (1) to 170 °C, add 2 weight parts of epoxy soybean oil acrylate and 0.1 weight part of sulfur, and stir at a speed of 5000 r / min for 30 min; (3) Add 5 parts by weight of activated rubber powder, 1 part by weight of SEBS, and 2 parts by weight of APAO to the asphalt obtained in step (2), and perform high-speed shearing at a rate of 180 °C and 5000 r / min for 1 h; (4) Add 0.5 part by weight of graphene oxide and 1 part by weight of organic montmorillonite to the asphalt obtained in step (3), and perform high-speed shearing at a rotation speed of 180 °C and 5000 r / min for 2 h. After the shearing is completed, develop at 170 °C for 2 h to obtain polyphosphoric acid-polymer composite modified asphalt.
[0050] Example 2 A preparation method of polyphosphoric acid-polymer composite modified asphalt, the preparation method comprising the following steps: (1) Heat 100 parts by weight of matrix asphalt to 165 °C, add 1.5 parts by weight of polyphosphoric acid to the matrix asphalt, and perform high-speed shearing at a rotation speed of 5300 r / min until evenly dispersed. After the shearing is completed, develop at 165 °C for 30 min; (2) Heat the asphalt obtained in step (1) to 175 °C, add 2.5 parts by weight of epoxy soybean oil acrylate and 0.3 part by weight of sulfur, and stir at a rotation speed of 5300 r / min for 30 min; (3) Add 10 parts by weight of activated rubber powder, 3 parts by weight of SEBS, and 3.5 parts by weight of APAO to the asphalt obtained in step (2), and perform high-speed shearing at a rate of 180 °C and 5000 r / min for 1 h; (4) Add 1.2 parts by weight of graphene oxide and 2 parts by weight of organic montmorillonite to the asphalt obtained in step (3), and perform high-speed shearing at a rotation speed of 180 °C and 5300 r / min for 2 h. After the shearing is completed, develop at 175 °C for 2 h to obtain polyphosphoric acid-polymer composite modified asphalt.
[0051] Example 3 A preparation method of polyphosphoric acid-polymer composite modified asphalt, the preparation method comprising the following steps: (1) Heat 100 parts by weight of matrix asphalt to 165 °C, add 3 parts by weight of polyphosphoric acid to the matrix asphalt, and perform high-speed shearing at a rotation speed of 5300 r / min until evenly dispersed. After the shearing is completed, develop at 165 °C for 30 min; (2) Heat the asphalt obtained in step (1) to 175 °C, add 5 parts by weight of epoxy soybean oil acrylate and 0.5 part by weight of sulfur, and stir at a rotation speed of 5300 r / min for 30 min; (3) Add 15 parts by weight of activated rubber powder, 5 parts by weight of SEBS, and 5 parts by weight of APAO to the asphalt obtained in step (2), and perform high-speed shearing at a rate of 180 °C and 5000 r / min for 1 h; (4) Add 2 parts by weight of graphene oxide and 3 parts by weight of organic montmorillonite to the asphalt obtained in step (3), and maintain a high-speed shear at 180 °C and a rotation speed of 5300 r / min for 2 h. After the shear is completed, develop at 175 °C for 2 h to obtain polyphosphoric acid-polymer composite modified asphalt.
[0052] Comparative Example 1 A preparation method of polyphosphoric acid-polymer composite modified asphalt, the preparation method comprising the following steps: The difference from Example 2 is: (1) Heat 100 parts by weight of base asphalt to 165 °C, add 1.5 parts by weight of polyphosphoric acid to the base asphalt, and perform high-speed shear at a rotation speed of 5300 r / min until evenly dispersed. After the shear is completed, develop at 165 °C for 30 min; (2) Heat the asphalt obtained in step (1) to 175 °C, add 5.1 parts by weight of epoxy soybean oil acrylate and 0.6 parts by weight of sulfur, and stir at a rotation speed of 5300 r / min for 30 min; (3) Add 16 parts by weight of activated rubber powder, 6 parts by weight of SEBS and 3.5 parts by weight of APAO to the asphalt obtained in step (2), and maintain a high-speed shear at 180 °C and a rate of 5000 r / min for 1 h; (4) Add 1.2 parts by weight of graphene oxide and 2 parts by weight of organic montmorillonite to the asphalt obtained in step (3), and maintain a high-speed shear at 180 °C and a rotation speed of 5300 r / min for 2 h. After the shear is completed, develop at 175 °C for 2 h to obtain polyphosphoric acid-polymer composite modified asphalt.
[0053] Comparative Example 2 A preparation method of polyphosphoric acid-polymer composite modified asphalt, the preparation method comprising the following steps: (1) Heat 100 parts by weight of base asphalt to 165 °C, add 0.4 parts by weight of polyphosphoric acid to the base asphalt, and perform high-speed shear at a rotation speed of 5300 r / min until evenly dispersed. After the shear is completed, develop at 165 °C for 30 min; (2) Heat the asphalt obtained in step (1) to 175 °C, add 1.9 parts by weight of epoxy soybean oil acrylate and 0.3 parts by weight of sulfur, and stir at a rotation speed of 5300 r / min for 30 min; (3) Add 10 parts by weight of activated rubber powder, 0.9 parts by weight of SEBS and 3.5 parts by weight of APAO to the asphalt obtained in step (2), and maintain a high-speed shear at 180 °C and a rate of 5000 r / min for 1 h; (4) Add 0.4 parts by weight of graphene oxide and 2 parts by weight of organic montmorillonite to the asphalt obtained in step (3), and perform high-speed shearing at 180 °C and a rotation speed of 5300 r / min for 2 h. After the shearing is completed, develop at 175 °C for 2 h to obtain polyphosphoric acid-polymer composite modified asphalt.
[0054] Experimental Example 1 Detect the properties of the polyphosphoric acid-polymer composite modified asphalt obtained in Examples 1-3, Comparative Example 1, and Comparative Example 2, specifically including: penetration (100 g, 25 °C, 5 s), softening point, ductility at 5 °C, rutting factor high temperature index, creep stiffness modulus (-18 °C), creep rate (-18 °C), softening point difference (163 °C), elastic recovery rate (25 °C, 1 h), and short-term aging (163 °C, 5 h) performance. Each test was carried out at least 3 parallel tests, and the average value was taken to obtain the test results shown in Table 1.
[0055] The performance detection adopts the detection methods and standards of JTG E20-2011 "Test Regulations for Asphalt and Asphalt Mixtures in Highway Engineering".
[0056] Table 1
[0057] As can be seen from Table 1, the polyphosphoric acid-polymer composite modified asphalt provided by the present application solves the problems of poor low-temperature performance of polyphosphoric acid modified asphalt, insufficient stability of SEBS modified asphalt, and poor interfacial compatibility between activated rubber powder and asphalt through the modification of the matrix asphalt by various modifiers. Under the co-modification of acrylate (ACR) and SEBS modifiers, they are intertwined in the matrix asphalt, while increasing the viscosity of the asphalt, forming a relatively stable cross-linked structure, and the synergy of polyphosphoric acid, epoxy soybean oil, and activated rubber powder improves the stability and consistency of the modified asphalt, thereby enhancing the storage stability performance; greatly improves the performance of the market-modified asphalt after aging; the SEBS molecules can still maintain an elastic state to toughen the asphalt after aging, and the functions of graphene oxide and organic montmorillonite enable the asphalt to have good low-temperature crack resistance and stress relaxation ability to be maintained.
[0058] Example 4 A preparation method of polyphosphoric acid-polymer composite modified asphalt, the preparation method includes the following steps: The difference from Example 2 is that: (4) Add 0.05 parts by weight of an anti-cracking agent. First, add benzoic anhydride to the asphalt obtained in step (3) to make the pH value of the reaction system 5.5, stir at a speed of 3000 r / min for 5 min, then add nonylphenol polyoxyethylene ether and 1-amino-8-naphthol-4,6-disulfonic acid, and stir at a speed of 5000 r / min for 20 min; the mass ratio of nonylphenol polyoxyethylene ether to 1-amino-8-naphthol-4,6-disulfonic acid is 1:1; (5) Add 2 parts by weight of graphene oxide and 3 parts by weight of organic montmorillonite to the asphalt obtained in step (4), and maintain a high-speed shear at 180 °C and a speed of 5300 r / min for 2 h. After the shearing is completed, develop at 175 °C for 2 h to obtain a polyphosphoric acid-polymer composite modified asphalt.
[0059] Example 5 A preparation method of a polyphosphoric acid-polymer composite modified asphalt, the preparation method comprising the following steps: The difference from Example 2 is: (4) Add 0.2 parts by weight of an anti-cracking agent. First, add benzoic anhydride to the asphalt obtained in step (3) to make the pH value of the reaction system 6.5, stir at a speed of 4000 r / min for 7 min, then add nonylphenol polyoxyethylene ether and 1-amino-8-naphthol-4,6-disulfonic acid, and stir at a speed of 5300 r / min for 25 min; the mass ratio of nonylphenol polyoxyethylene ether to 1-amino-8-naphthol-4,6-disulfonic acid is 1:1.5; (5) Add 2 parts by weight of graphene oxide and 3 parts by weight of organic montmorillonite to the asphalt obtained in step (4), and maintain a high-speed shear at 180 °C and a speed of 5300 r / min for 2 h. After the shearing is completed, develop at 175 °C for 2 h to obtain a polyphosphoric acid-polymer composite modified asphalt.
[0060] Example 6 A preparation method of a polyphosphoric acid-polymer composite modified asphalt, the preparation method comprising the following steps: The difference from Example 2 is: (4) Add 0.4 parts by weight of an anti-cracking agent. First, add benzoic anhydride to the asphalt obtained in step (3) to make the pH value of the reaction system 7, stir at a speed of 5000 r / min for 10 min, then add nonylphenol polyoxyethylene ether and 1-amino-8-naphthol-4,6-disulfonic acid, and stir at a speed of 5000 r / min for 30 min; the mass ratio of nonylphenol polyoxyethylene ether to 1-amino-8-naphthol-4,6-disulfonic acid is 1:2.5; (5) Add 2 parts by weight of graphene oxide and 3 parts by weight of organic montmorillonite to the asphalt obtained in step (4), and maintain a high-speed shear at 180 °C and a rotation speed of 5300 r / min for 2 h. After the shearing is completed, develop at 175 °C for 2 h to obtain a polyphosphoric acid-polymer composite modified asphalt.
[0061] Comparative Example 3 A preparation method of a polyphosphoric acid-polymer composite modified asphalt, the preparation method comprising the following steps: The difference from Example 5 is that: (4) Add benzoic anhydride to the asphalt obtained in step (3) to make the pH value of the reaction system 5, stir at a rotation speed of 5000 r / min for 10 min, then add nonylphenol polyoxyethylene ether and 1-amino-8-naphthol-4,6-disulfonic acid, and stir at a rotation speed of 5000 r / min for 30 min; the mass ratio of nonylphenol polyoxyethylene ether to 1-amino-8-naphthol-4,6-disulfonic acid is 1:2.5.
[0062] Comparative Example 4 A preparation method of a polyphosphoric acid-polymer composite modified asphalt, the preparation method comprising the following steps: The difference from Example 5 is that: (4) Add benzoic anhydride to the asphalt obtained in step (3) to make the pH value of the reaction system 7.2, stir at a rotation speed of 5000 r / min for 10 min, then add nonylphenol polyoxyethylene ether and 1-amino-8-naphthol-4,6-disulfonic acid, and stir at a rotation speed of 5000 r / min for 30 min; the mass ratio of nonylphenol polyoxyethylene ether to 1-amino-8-naphthol-4,6-disulfonic acid is 1:2.5.
[0063] Experimental Example 2 Detect the performance of the polyphosphoric acid-polymer composite modified asphalt obtained in Example 5, Comparative Example 3, and Comparative Example 4, specifically including: penetration (100 g, 25 °C, 5 s), softening point, ductility at 5 °C, rutting factor high temperature index, creep stiffness modulus (-18 °C), creep rate (-18 °C), softening point difference (163 °C), elastic recovery rate (25 °C, 1 h), and short-term aging (163 °C, 5 h) performance. Each test is carried out at least 3 parallel tests, and the average value is taken to obtain the test results as shown in Table 2.
[0064] The performance detection adopts the detection methods and standards of JTG E20-2011 "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering".
[0065] Table 2
[0066] As can be seen from Table 2, after adding crack resistance agents, including benzoic anhydride, nonylphenol polyoxyethylene ether, and 1-amino-8-naphthol-4,6-disulfonic acid, the low-temperature performance of the modified asphalt is significantly improved. By comparing Example 5 with Examples 1-3, it can be seen that after adding the crack resistance agent, the penetration, softening point, and ductility of the modified asphalt obtained in Example 3 are significantly higher than those in Examples 1-3. The increase in penetration indicates that under low-temperature conditions, the modified asphalt provided in Example 5 is more likely to flow, showing better low-temperature ductility and crack resistance. The higher the ductility of asphalt at low temperature, the better the low-temperature performance of the modified asphalt. During the use of asphalt, the crack resistance of the modified asphalt pavement at low temperature is enhanced, improving the deficiencies in low-temperature ductility and crack resistance of the polyphosphoric acid-modified asphalt, where the pavement is prone to embrittlement, crusting, and arching, enabling the pavement to maintain flatness at low temperature.
[0067] Meanwhile, by comparing Example 5 with Comparative Examples 3 and 4, benzoic anhydride can adjust the acidity and alkalinity during the preparation of the modified asphalt, keeping the pH value of the system between 5.5 and 7 before adding nonylphenol polyoxyethylene ether and 1-amino-8-naphthol-4,6-disulfonic acid. A suitable acid-base environment is conducive to the reaction of nonylphenol polyoxyethylene ether and 1-amino-8-naphthol-4,6-disulfonic acid with asphalt, facilitating the stable formation of a multiphase composite structure to ensure the low-temperature stability and crack resistance of the modified asphalt.
[0068] Comparative Example 5 A preparation method of a polyphosphoric acid-polymer composite modified asphalt, the preparation method comprising the following steps: The difference from Example 5 is: (4) Add 0.2 parts by weight of a crack resistance agent, add nonylphenol polyoxyethylene ether and 1-amino-8-naphthol-4,6-disulfonic acid to the asphalt obtained in step (3), and stir at a speed of 5300 r / min for 25 min; the mass ratio of nonylphenol polyoxyethylene ether to 1-amino-8-naphthol-4,6-disulfonic acid is 1:1.5.
[0069] Comparative Example 6 A preparation method of a polyphosphoric acid-polymer composite modified asphalt, the preparation method comprising the following steps: The difference from Example 5 is: (4) Add 0.2 parts by weight of a crack resistance agent, first add benzoic anhydride to the asphalt obtained in step (3) to make the pH value of the reaction system 6.5, stir at a speed of 4000 r / min for 7 min, then add 1-amino-8-naphthol-4,6-disulfonic acid, and stir at a speed of 5300 r / min for 25 min.
[0070] Comparative Example 7 A preparation method of polyphosphoric acid-polymer composite modified asphalt, the preparation method comprising the following steps: The difference from Example 5 is that: (4) Add 0.2 parts by weight of an anti-cracking agent. First, add benzoic anhydride to the asphalt obtained in step (3) to make the pH value of the reaction system 6.5, stir at a speed of 4000 r / min for 7 min, then add 1-amino-8-naphthol-4,6-disulfonic acid, and stir at a speed of 5300 r / min for 25 min.
[0071] Experimental Example 3 Detect the properties of the polyphosphoric acid-polymer composite modified asphalt obtained in Example 5 and Comparative Examples 5-7, specifically including: penetration (100 g, 25 °C, 5 s), softening point, ductility at 5 °C, rutting factor high-temperature index, creep stiffness modulus (-18 °C), creep rate (-18 °C), softening point difference (163 °C), elastic recovery rate (25 °C, 1 h), and short-term aging (163 °C, 5 h) properties. Each test was carried out at least 3 parallel tests, and the average value was taken to obtain the test results as shown in Table 3.
[0072] The performance detection adopts the detection methods and standards of JTG E20-2011 "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering".
[0073] Table 3
[0074] As can be seen from Table 3, by adding nonylphenol polyoxyethylene ether, benzoic anhydride and 1-amino-8-naphthol-4,6-disulfonic acid simultaneously, the low-temperature performance of the modified asphalt is significantly improved, especially the penetration, softening point and elastic recovery rate, indicating that the hydroxyl groups contained in nonylphenol polyoxyethylene ether can react with the surface active groups of asphalt, and some of the amino, hydroxyl and sulfonic acid groups in 1-amino-8-naphthol-4,6-disulfonic acid react with the active sites on the surface of asphalt to further modify the asphalt. The remaining 1-amino-8-naphthol-4,6-disulfonic acid is wrapped on the outer surface of the asphalt particles modified by SEBS and PPA. A multiphase composite structure is formed between each modifier and asphalt. When the modified asphalt is used in a low-temperature environment, the composite structures can buffer the stress generated by low temperature with each other, thereby improving the low-temperature performance of the modified asphalt and reducing the embrittlement and cracking of the modified asphalt due to temperature reduction.
[0075] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application has been described in detail with reference to the foregoing embodiments, those of ordinary skill in the art should understand that they can still modify the technical solutions described in the foregoing embodiments, or perform equivalent replacements on some or all of the technical features; and these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
Claims
1. A polyphosphoric acid-polymer composite modified asphalt, characterized in that, Raw materials comprising the following components by weight parts: Matrix asphalt 100 weight parts, polyphosphoric acid 0.5 - 3 weight parts, stabilizer 0.1 - 0.5 weight parts, bio-based plasticizer 2 - 5 weight parts, elastomer particles 5 - 15 weight parts, nano-enhanced filler 0.5 - 2 weight parts, SEBS 1 - 5 weight parts, APAO 2 - 5 weight parts, organic montmorillonite 1 - 3 weight parts.
2. The polyphosphoric acid-polymer composite modified asphalt according to claim 1, characterized in that, An anti-cracking agent in an amount of 0.05 - 0.4 weight parts is further added to the asphalt, and the anti-cracking agent is obtained by mixing nonylphenol polyoxyethylene ether, benzoic anhydride and 1-amino-8-naphthol-4,6-disulfonic acid in a mass ratio of 1:0.55 - 4.5:1 - 2.
5.
3. The polyphosphoric acid-polymer composite modified asphalt according to claim 1, characterized in that, The polyphosphoric acid is an industrial pure reagent, and the purity is not less than 85% calculated by phosphorus pentoxide content.
4. The polyphosphoric acid-polymer composite modified asphalt according to claim 1, characterized in that, The stabilizer is selected from sulfur or an organosilane coupling agent.
5. The polyphosphoric acid-polymer composite modified asphalt according to claim 1, characterized in that, The bio-based plasticizer is selected from epoxy soybean oil acrylate.
6. The polyphosphoric acid-polymer composite modified asphalt according to claim 5, characterized in that, The epoxy value of the epoxy soybean oil acrylate is 6.0% - 6.5%.
7. The polyphosphoric acid-polymer composite modified asphalt according to claim 1, characterized in that, The elastomer particles are selected from activated rubber powder, and the particle size of the activated rubber powder is 80 - 120 mesh.
8. The polyphosphoric acid-polymer composite modified asphalt according to claim 1, characterized in that, The nano-enhanced filler includes at least one of graphene oxide and nano-zinc oxide.
9. The polyphosphoric acid-polymer composite modified asphalt according to any one of claims 1-8, characterized in that, The matrix asphalt includes one or more of 70# matrix asphalt, 110# matrix asphalt, 130# matrix asphalt and 140# matrix asphalt.
10. A preparation method of a polyphosphoric acid-polymer composite modified asphalt, characterized in that, The method is used to prepare the modified asphalt as described in any one of claims 1 - 9, and the preparation method includes the following steps: (1) By weight parts, heat the matrix asphalt to 160 - 170 °C, add polyphosphoric acid to the matrix asphalt, and shear at a speed of 5000 - 5500 r / min until evenly dispersed. After the shearing is completed, develop at 165 °C for 30 min; (2) Heat the asphalt obtained in step (1) to 170 - 180 °C, add the bio-based plasticizer and stabilizer by weight parts, and stir at a speed of 5000 - 5500 r / min for 30 min; (3) By weight parts, add the activated rubber powder, SEBS and APAO to the asphalt obtained in step (2), and maintain a high-speed shearing at a rate of 180 °C and 5000 r / min for 1 h; (4) By weight parts, add benzoic anhydride to the asphalt obtained in step (3), stir at a speed of 3000 - 5000 r / min for 5 - 10 min to keep the pH value of the system at 5.5 - 7, then add nonylphenol polyoxyethylene ether and 1-amino-8-naphthol-4,6-disulfonic acid, and stir at a speed of 5000 - 5500 r / min for 20 - 30 min; (5) Add the nano-filler and organic montmorillonite to the asphalt obtained in step (4), and maintain a high-speed shearing at a rate of 180 °C and 5000 - 5500 r / min for 2 h. After the shearing is completed, develop at 170 - 180 °C for 2 h to obtain a polyphosphoric acid-polymer composite modified asphalt.
Citation Information
Patent Citations
Traffic anti-track asphalt modifier and its modified asphalt and asphalt mixture
CN101165102A
SBS / PE (styrene-butadiene-styrene / polyethylene) modified asphalt material
CN104910637A
APAO waste rubber powder composite modified asphalt and manufacturing method and application thereof
CN106221251A
Composite modified asphalt based on SEBS and rubber powder and preparation method thereof
CN108003638A
Preparation method of polyurethane / organic montmorillonite composite modified asphalt
CN108485292A
Cited By
Low-carbon modified emulsified asphalt based on bio-based ester and preparation method of low-carbon modified emulsified asphalt
CN120988497A